2023
DOI: 10.3390/vaccines11030596
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Inactivated Avian Influenza Virus Vaccine against Circulating H9N2 in Chickens and Ducks

Abstract: Avian influenza virus (AIV) subtype H9N2 is the most widespread AIV in poultry worldwide, causing great economic losses in the global poultry industry. Chickens and ducks are the major hosts and play essential roles in the transmission and evolution of H9N2 AIV. Vaccines are considered an effective strategy for fighting H9N2 infection. However, due to the differences in immune responses to infection, vaccines against H9N2 AIV suitable for use in both chickens and ducks have not been well studied. This study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our immune protection experiments confirmed that the self-developed vaccine showed better resistance to infection by epidemic strains, significantly reducing the morbidity rate, decreasing pathological damage, reducing shedding, and virus loads in tissues. Our vaccine was similar to other strains in that high titers of virus were still detected in the lungs and trachea on the fifth day after challenge and 75% of chicken throat swabs still contained virus ( Liu et al, 2023 ), which led to nonimmune chickens in the same house being infected by the shedding virus. However, it is worth noting that our vaccine can prevent chickens from shedding viruses through the cloacal cavity (the separation rate of the cloacal swabs is 0%), which may be that the vaccine can reduce or eliminate virus replication in the intestine.…”
Section: Discussionmentioning
confidence: 74%
“…Our immune protection experiments confirmed that the self-developed vaccine showed better resistance to infection by epidemic strains, significantly reducing the morbidity rate, decreasing pathological damage, reducing shedding, and virus loads in tissues. Our vaccine was similar to other strains in that high titers of virus were still detected in the lungs and trachea on the fifth day after challenge and 75% of chicken throat swabs still contained virus ( Liu et al, 2023 ), which led to nonimmune chickens in the same house being infected by the shedding virus. However, it is worth noting that our vaccine can prevent chickens from shedding viruses through the cloacal cavity (the separation rate of the cloacal swabs is 0%), which may be that the vaccine can reduce or eliminate virus replication in the intestine.…”
Section: Discussionmentioning
confidence: 74%
“…Poultry vaccination is highly valuable in combating avian influenza and controlling the spread of the virus. 132 Vaccinated chickens were found to have high antibody titres after a single dose only, suggesting that protective immunity can be induced with one single dose in chicken. In contrast, ducks and geese produced a drastically low antibody titre compared to chickens after the first vaccine shot.…”
Section: Biosafety Biosecurity Measures To Control and Counter Back A...mentioning
confidence: 99%
“…Aside from biosecurity, as mentioned earlier, vaccination is the most essential scheme. Poultry vaccination is highly valuable in combating avian influenza and controlling the spread of the virus 132 . Vaccinated chickens were found to have high antibody titres after a single dose only, suggesting that protective immunity can be induced with one single dose in chicken.…”
Section: Biosafety Biosecurity Measures To Control and Counter Back A...mentioning
confidence: 99%